The Cognitive Representation of SHAME in Lithuanian and Polish Paremias - Bogdzevič, Monika (Tautosakos darbai, 2019)
The article provides a glimpse at wider research on the conceptualization of shame, fear and anger in Lithuanian language. The author attempts to present the semantic and axiological substance of Lithuanian gėda and Polish wstyd (Eng. shame, embarrassment) encoded in the consciousness of two different – namely, Lithuanian and Polish – linguistic-cultural communities.The cognitive representation of the concepts mentioned above has been construed by applying S-A-T methodology, proposed by Jerzy Bartmiński. The data have been drawn from dictionaries and paremias collected from the compendiums of Lithuanian and Polish proverbs by searching for the conceptual and lexical keys of gėda and wstyd. Examination of the lexical data sketches the semantic core of gėda and wstyd, while the semantic analysis of paremias reflects its textual potential, giving an insight into its ethno-conceptualization.Thus, the construct of the mental image of shame illustrated in the Lithuanian and Polish proverbs under study draws on the dictionary definitions of the lexemes, and on semantic analysis of paremias containing those lexemes. The study concludes with a synthetic definition of the Lithuanian gėda and Polish wstyd with an emphasis on its similarities and differences, entrenched in proverbs and language systems as well.
Keywords: cognitive definition; concept of shame; ethnolinguistics; paremia